Modifiable risk factors and overall cardiovascular mortality: Moderation of urbanization - Sajid, Mirza Rizwan; Noryanti, Muhammad; Roslinazairimah, Zakaria; Bukhari, Syed Ahmad Chan (PAGEPress, 2020)
Background: Modifiable risk factors are associated with cardiovascular mortality (CVM) which is a leading form of global mortality. However, diverse nature of urbanization and its objective measurement can modify their relationship. This study aims to investigate the moderating role of urbanization in the relationship of combined exposure (CE) of modifiable risk factors and CVM.